1986
DOI: 10.1002/zaac.19865320110
|View full text |Cite
|
Sign up to set email alerts
|

Zur Möglichkeit der planaren Tetrakoordination von Elementen der IV. Hauptgruppe (C, Si, Ge)

Abstract: Mit Hilfe semiempirischer Rechenverfahren (CNDO/2, EHT) wurde die Fähigkeit von Silicium und zum Vergleich von Kohlenstoff und Germanium zur planaren Tetrakoordination überprüft. Es wurden Rechnungen für die tetraedrischen Grundzustandsstrukturen (Td – Symmetrie) sowie für die künstlich planar gehaltenen Strukturen (D4h – Symmetrie) der Verbindungen CH4, SiH4, GeH4 und CF4, SiF4, GeF4 durchgeführt. Alle planaren Spezies sind im Vergleich zu den Tetraederstrukturen instabiler, haben größere Bindungsabstände und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Early semi-empirical (CNDO/2, ETH) calculations on T d and D 4h symmetry EH 4 and EF 4 (E = C, Si, Ge) showed that it is easier to form planar structures as one increases the atomic number of the central atom and with increasing electronegativity of the substituents. [130] Recent examples include hydrometal complexes Pd 5 H 5 Ge À (29 j), Pt 5 H 5 Ge À (29 l), [68b] Cu 6 H 6 Ge (51) [127] ,a nd the boron wheel B 9 Ge + . [83] Pentatomic planar tetracoordinate silicon-and germanium-containing molecules SiAl 4 À (4k)a nd GeAl 4 À (4l; Figure 4) were experimentally detected in 2000.…”
Section: Silicon and Germaniummentioning
confidence: 99%
See 1 more Smart Citation
“…Early semi-empirical (CNDO/2, ETH) calculations on T d and D 4h symmetry EH 4 and EF 4 (E = C, Si, Ge) showed that it is easier to form planar structures as one increases the atomic number of the central atom and with increasing electronegativity of the substituents. [130] Recent examples include hydrometal complexes Pd 5 H 5 Ge À (29 j), Pt 5 H 5 Ge À (29 l), [68b] Cu 6 H 6 Ge (51) [127] ,a nd the boron wheel B 9 Ge + . [83] Pentatomic planar tetracoordinate silicon-and germanium-containing molecules SiAl 4 À (4k)a nd GeAl 4 À (4l; Figure 4) were experimentally detected in 2000.…”
Section: Silicon and Germaniummentioning
confidence: 99%
“…Compared with silicon, planar hypercoordinate germanium has rarely been investigated. Early semi‐empirical (CNDO/2, ETH) calculations on T d and D 4 h symmetry EH 4 and EF 4 (E=C, Si, Ge) showed that it is easier to form planar structures as one increases the atomic number of the central atom and with increasing electronegativity of the substituents 130. Recent examples include hydrometal complexes Pd 5 H 5 Ge − ( 29 j ), Pt 5 H 5 Ge − ( 29 l ),68b Cu 6 H 6 Ge ( 51 )127, and the boron wheel B 9 Ge + 83…”
Section: Other Planar Tetracoordinate (Or Hypercoordinate) Elementsmentioning
confidence: 99%
“…Im Vergleich zu Silicium wurde planar hyperkoordiniertes Germanium nur selten untersucht. Frühe semiempirische Rechnungen (CNDO/2, EHT) zu den T d ‐ und D 4 h ‐symmetrischen Spezies EH 4 und EF 4 (E=C, Si, Ge) zeigten, dass es einfacher ist, planare Strukturen zu schaffen, wenn man die Ordnungszahl des Zentralatoms und die Elektronegativität der Substituenten erhöht 130. Neuere Beispiele beinhalten die Hydrometallkomplexe Pd 5 H 5 Ge − ( 29 j ), Pt 5 H 5 Ge − ( 29 l ),68b Cu 6 H 6 Ge ( 51 )127 und das Borrad B 9 Ge + 83…”
Section: Andere Planar Tetrakoordinierte (Oder Hyperkoordinierte) unclassified